Effects of Livelihood Empowerment against Poverty (Leap) on Beneficiaries in Kwaebibirem Municipality. - Otchere , Samuel Nyamekye (International Journal of Humanity and Social Sciences, 2024)
Background: Ghana has assented to many international conventions and has passed national legislation that obliges the government to find practical expressions to cater to civil and political rights and its citizens' economic, social, and cultural rights. To meet these legal requirements, the Government of Ghana has drafted and is implementing a National Social Protection Strategy to protect its vulnerable populace. A major element of this strategy is the Livelihood Empowerment Against Poverty (LEAP). LEAP is a direct cash transfer programme, which targets about a quarter of Ghana's populace hit with extreme poverty due to their state of being vulnerable, old age or orphans. The study was conducted in the Kwaebibirem Municipality of the Eastern Region to unearth Livelihood Empowerment against Poverty (LEAP)’s effect on the beneficiaries and the shortcomings since its implementation. Methodology: This study employed the mixed-method research approach. A purposive sampling technique was used to select 40 respondents. Data were obtained from all sources. Findings: The study revealed that the cash transfer system, despite its challenges, tends to have more positive effects on the beneficiaries. Findings reveal general operational challenges such as depoliticization, delays in cash disbursement for payment and sensitization. Unique Contribution to Theory, Practice and Policy: The study recommends that the Ministry of Gender and Social Protection decentralize LEAP activities.